The Protective Effect of Propolis Nanoemulsion (NEP) Against UVB Irradiation Induced Photoaging in Human Dermal Fibroblast (HDF) - Anggraini Barlian; Rini Agustin; Ramadhani Eka Putra (3BIO: Journal of Biological Science, Technology and Management, 2020)
The skin damage induced by UV irradiation can cause photoaging as a consequence of reactive oxygen species (ROS) generation. Propolis is one of the most abundant natural product sources of polyphenols and derived from various plant resins collected by honeybees. This study aimed to determine the due administration of the propolis nanoemulsion (NEP) as an anti-photoaging by observing the concentration of intracellular ROS and lipid peroxides in human dermal fibroblast (HDF) by exposure to UVB. The cytotoxic of NEP was tested by the MTT assay, intracellular ROS was measured using the DCFDA assay, lipid peroxide products were analyzed by the TBARS assay and cell nuclei was observed by DAPI staining. PSA analysis revealed that the sizes of NEP were about 131.9 to 131 nm. The optimum concentration of NEP was 0,1Î¼g / ml. ROS production in HDF treatment of NEP significantly decreases (p <0.05). Lipid peroxide products showed the same pattern as ROS concentration. The lipid peroxide concentration in the treatment NEP significantly decreases (p<0.05). In conclusion, the propolis in NEP acts as an antioxidant and has the potential to reduce the production of ROS and lipid peroxides caused by exposure to UVB.